(untitled) (KALAA SAMIKSHA, 2025)
After India’s independence in 1947, the country’s art world entered a period of deep change. Artists were trying to define what it meant to be “modern” and “Indian” at the same time. Groups like the Progressive Artists’ Group explored bold, new styles and created a national art language that combined Indian themes with modernist approaches. But alongside this well-known path, a less talked-about but equally powerful change was happening: the rise of feminine sensibility in Indian art. This feminine sensibility wasn’t just about women becoming artists or painting female figures. It was about a new way of seeing the world, one that focused on emotion, care, inner life, the body, memory, struggle, and resilience. It brought attention to subjects that had often been ignored or seen as “unimportant”: the home, the daily lives of women, motherhood, pain, silence, and dreams. Many artists began using their work to question traditional roles, speak out against injustice, and reclaim the female body from being shown only as an object of beauty or desire. This article throws light on how feminine art in India helped change the way women were shown in art. It celebrated their strength, emotions, and daily lives. It questioned old ideas and opened doors for future artists to speak freely about equality and truth.